2021
DOI: 10.4103/jmas.jmas_221_20
|View full text |Cite
|
Sign up to set email alerts
|

A case of unusual evisceration through laparoscopic port site

Abstract: Drain site eviscerations have been reported as a rare complication following abdominal surgery. An 82-year-old women was diagnosed with carcinoma stomach and underwent laparoscopic subtotal gastrectomy. A few hours following removal of the duodenal stump drain, she developed small bowel evisceration through the drain site. It was successfully managed with immediate bedside release of fascial constriction followed by definitive repair later. Although herniations and eviscerations via larger drain sites have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…However, there are rare reports of DSH at the 5 mm port site. Moreaux et al [ 13 ] and James et al [ 14 ] reported cases which occurred at the 5 mm port site from several hours to several days after the drainage tube was removed. These cases were largely caused by the suction effect resulting from drain removal and a postoperative complication ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are rare reports of DSH at the 5 mm port site. Moreaux et al [ 13 ] and James et al [ 14 ] reported cases which occurred at the 5 mm port site from several hours to several days after the drainage tube was removed. These cases were largely caused by the suction effect resulting from drain removal and a postoperative complication ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These were the omentum, gallbladder, appendix vermiformis, fallopian tube, and small bowel. In the aforementioned cases, evisceration occurred three to eight hours post-operation [2,[6][7][8]11,14]. Drain site eviscerations along with the drain have not yet been reported as a complication following open abdominal or laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the imminent risk of strangulation and subsequent necrosis of the eviscerated organ, drain site evisceration requires immediate intervention. Mathew et al proposed a bedside reduction of the strangulated, ischemic small bowel under local anaesthesia after extending the drain site incision and simultaneous resuscitation with warm gauze and 100% oxygen [2]. Spartalis et al performed, on an urgent basis, a bedside appendectomy under sterile conditions, without anaesthesia or extending the drain site incision [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations